Reflexe národa a vlastenectví: (Postoj obyvatel tří českých měst na počátku 21.století) - Moravcová, Mirjam (Lidé města, 2005)
Miroslav Hroch’s article “Nation as a cultural construct?” has served as an impetus for a reflection about the meaning currently associated, by Czech spokesmen, with the emotional relationship to a national society. Using this posed question, I return to the problem of actual reflection of symbols that have been accepted by modern Czech society in course of national-emancipation, as well as national-political struggles. I revisit the problem of relationship of a contemporary person to symbols that were manipulated by Czech elite during formation of national awareness and that were used in various interactions in course of strengthening the relationship between a person and national society. This reflection is structured considering the nature of data that have been collected by means of a questionnaire originally designed for a different research goal. The goal of this research was to map attitudes of Czech spokesmen regarding two phenomena: a) existence of the nation, and b) national minorities, ethnic and immigration groups in Czech Republic. Through questions targeting opinions about the actual meaning of a nation and patriotism, we have also gathered testimony not only about emotional relationship of Czech spokesmen to the Czech society but also about symbols that evoke this relationship.